Estudo do desempenho de redes de distribuição rural utilizando dados do sistema de localização de tempestades e da operação do sistema: uma abordagem de Engenharia - Afonso Ferreira Avila (2005)
The work presents the results of a study based on the application of Lightning Location System (LLS) data and Interruptions data to analyze actual lighting performance of rural distribution lines at Minas Gerais State. The work presents the data used in the development of the case study consisting of three sources of infor mation: lightning data, extracted from LLS records; interruption data extracted from CONINT (a CEMIGs Interruption Control System) reports; topology data and location the protection equipment, supplied by GEMINI (a CEMIGs Management Network System). The present work is based on the analysis of 5.379 interruptions and 737.747 lighting events recorded from 2001 to 2004. The method consists of three stages: (1) lightning performance calculation, (2) analysis of lightning activity and system interruptions and (3) the correlation between them. The calculation process is based on the procedure of IEEE Standard 1410. A case study is presented to show how different factors, such as structure degree of exposure (direct and indirect strikes), overvoltage levels and the basic insulation level affect the lightning performance of the distribution lines. The observed and calculated values are presented and compared for real networks different Basic Insulation Level (BIL). The results demonstrate the usefulness of the proposed methodology as an evaluation tool for distribution network performance analysis.